2021
DOI: 10.3390/v13122400
|View full text |Cite
|
Sign up to set email alerts
|

Oral Selective TLR8 Agonist Selgantolimod Induces Multiple Immune Cell Responses in Humans

Abstract: TLR8 agonists have the potential for use as immunomodulatory components in therapeutic modalities for viral infections such as chronic HBV (CHB) and HIV. In this study, using peripheral blood samples from a phase 1a clinical trial, we examined the acute effects of a single oral administration of a selective TLR8 agonist on immune cell phenotypes. Administration of the TLR8 agonist selgantolimod (SLGN) in healthy individuals resulted in alteration in frequencies of peripheral blood monocytes, pDCs, mDCs and MAI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Myeloid cell activation was evident by the upregulated expression of co-stimulatory molecules CD40 and CD86, accompanied by the production of IL-6 and IL-18 from these cells. Concomitantly, there was induction of the early activation marker CD69 on innate and adaptive lymphoid cells and enhanced expression of the effector molecules granzyme B and perforin [175]. Furthermore, the phase Ia study also showed that the single doses of up to 5 mg GS-9688 were safe and induced dose-dependent pharmacodynamics responses [176].…”
Section: Tlr7/8 Agonists Related Clinical Trialsmentioning
confidence: 95%
“…Myeloid cell activation was evident by the upregulated expression of co-stimulatory molecules CD40 and CD86, accompanied by the production of IL-6 and IL-18 from these cells. Concomitantly, there was induction of the early activation marker CD69 on innate and adaptive lymphoid cells and enhanced expression of the effector molecules granzyme B and perforin [175]. Furthermore, the phase Ia study also showed that the single doses of up to 5 mg GS-9688 were safe and induced dose-dependent pharmacodynamics responses [176].…”
Section: Tlr7/8 Agonists Related Clinical Trialsmentioning
confidence: 95%
“…These immunostimulatory activities have been attributed to TLR8 based on studies in mice but mice do not accurately model TLR reactivity in humans (Table 1) and this finding is at odds with the well understood biochemical properties of oligonucleotides: TLR8 reacts to unmodified ssRNA and TLR reactivity to TLR7/8 is well shielded by 2 MOE modification in bepirovirsen. Moreover, the oral TLR8 antagonist selgantolimod (GS-9688) did not elicit any HBsAg responses in human infection [149] despite clear immunostimulatory effects [149,150].…”
Section: Aso/sirna Effects In Vitro In Vivo and In Humans In Hbv Infe...mentioning
confidence: 99%
“…Selgantolimod (GS-9688): Selgantolimod is a selective TLR-8 agonist with antiviral activity against chronic HBV infection. It leads to the production of proinflammatory cytokines, chemokines, and interferons that initiate an innate and adaptive immune response against HBV[ 66 ].…”
Section: Future Therapy For Hepatitis Bmentioning
confidence: 99%